The Legal and Social Aspect for Underage Marriage Women's Education Rights in the Perspective of Human Rights: Contemporary Issues and Problems - Arifin, Ridwan; Rodiyah, Rodiyah; Putri, Fadhilah Rizky Afriani (Sawwa: Jurnal Studi Gender, 2020)
The right to education is a fundamental human right and must be fulfilled by the state. However, the right to education, especially for women with underage marriages (child marriages), has not yet had adequate education. This paper aims to analyze the legal and social aspects of children's educational rights, especially women with conditions of underage marriage (child marriage) in Indonesia. This study examines the formal juridical aspects of the protection and guarantee of education rights for women and social aspects related to the constraints of fulfilling women's education. This research is a normative juridical study in which this study looks at the community's various facts based on the applicable legal rules. This research's social aspects are seen based on various social theories related to this research study; the data and facts obtained in this study are data sourced from previous research, both print and online media. This research confirms that child marriage is motivated by many factors, one of which is economic conditions so that women cannot achieve the rights to education. However, according to the 1945 Constitution Article 31 paragraph (1) that every citizen has the right to get an education. However, there are no strict criminal sanctions for families who leave their children out of school in terms of law enforcement.